Jaringan Drainase Kawasan Sesela Kecamatan Gunung Sari - Rina Septiana; Hermanto Hermanto; Suryawan Murtiadi (LPPM Universitas Mataram, 2020)
Sesela area is one of the areas in Gunung Sari district, West Lombok. In this Sesela area, there are puddles or floods that disturb the community, especially those in the area of Jati Sela Village. The purpose of this study was to determine the high rainfall, and the existing canal are still able to accommodate the flood discharge or not. In this study began with data collection namely primary data collection and secondary data collection. Then conduct data analysis, namely hydrological analysis and hydraulic analysis. Based on the results of hidrological analysis, the amaount of rain R2th was 86,298 mm and R5th was 108,642 mm. Based on the results of calculations with a 5 year return period (R5th) comparison of the results obtained flood discharge is greatest at Griya Praja Asri canal is equal to 1,872 m³sec⁻¹. While the calculation is based on 11 sections hydraulics existing canals, namely Johar Pelita canal, Griya Praja Asri canal, Pesona Raya 1 canal, Perum Elite Rinjani Asri canal, Pesona Raya 2 canal, Ireng Daye canal, Ireng Lauk 2 canal, Pesona Raya 3 canal, Jati Ireng canal, Ireng Lauk 1 canal, and Pesona Raya 4 canal almost all of them can not accommodate flood discharge, causing water overflow or puddles. To overcome the overflow of water that occurs in the canal, redimensions are carried out so that the canals can function optimally.